2017
DOI: 10.1515/amcs-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Nonlinear Time–Delayed Systems with Application to Biological Models

Abstract: In this paper, we analyse the local stability of a gene-regulatory network and immunotherapy for cancer modelled as nonlinear time-delay systems. A numerically generated kernel, using the sum-of-squares decomposition of multivariate polynomials, is used in the construction of an appropriate Lyapunov-Krasovskii functional for stability analysis of the networks around an equilibrium point. This analysis translates to verifying equivalent LMI conditions. A delay-independent asymptotic stability of a second-order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Kruthika et al [2] investigate the local stability of a gene-regulatory network and immunotherapy for cancer modeled in a nonlinear time-delay system. Many articles have appeared as collecting theorems homotopy methods for solutions that concerned with the properties of delayed systems [3][4][5][6].…”
Section: Periodic Solution and Stability Behavior For Nonlinear Oscilmentioning
confidence: 99%
“…Kruthika et al [2] investigate the local stability of a gene-regulatory network and immunotherapy for cancer modeled in a nonlinear time-delay system. Many articles have appeared as collecting theorems homotopy methods for solutions that concerned with the properties of delayed systems [3][4][5][6].…”
Section: Periodic Solution and Stability Behavior For Nonlinear Oscilmentioning
confidence: 99%
“…The presence of the delay, an unstableness's factor, lead to a complex global stability for the delayed nonlinear systems, even more complicated than the delay free case, and it shares the same use of sufficient conditions with the free delay systems which represents a conservative way to analyze a system stability [6,36], however by optimizing the upper bound terms researchers try to improve results and minimize this conservativeness effect. Also, the stability conditions are splitted to delay dependent [13,23,36] or delay independent techniques [13,18,36].…”
Section: Problem Statement and Preliminariesmentioning
confidence: 99%
“…Independent delay conditions. Independent delay conditions are the simplest way to investigate a system stability, it relies on resolving LMIs without involving delay terms, which means theoretically, if such conditions exists, that the system will be stable for any delay value [13,18,36], but practically such conditions are hard and sometimes even impossible to find.…”
Section: Problem Statement and Preliminariesmentioning
confidence: 99%
“…The analysis showed that the oscillator vibrational energy could be transferred to the pendulum parametrically when the pendulum natural frequency is equal to one-half of the oscillator natural frequency. Kruthika et al [16] analyzed the local stability of a gene-regulatory network and immunotherapy of cancer. They are modeled as nonlinear time-delayed systems.…”
Section: Introductionmentioning
confidence: 99%